Kinematic Parameters of the Biplanetary Mechanism (Intermittent Mixing Machines) - Nematov, Erkin; Berdiev, Amon; Wang, Peng (Manufacturing Technology Journal, 2023)
The subject of research is the kinematic parameters of a biplanetary mechanism of the intermitted mixing machines. The article substantiates analytical expressions for determining the kinematic parameters of the drives of the working body of the intermitted mixing machines with planetary ones with double satellites and biplanetary mechanisms; the laws of change of displacements, velocities and accelerations of the points of the working body for drives with planetary one with double satellites and biplanetary mechanisms are determined; the regularities of the influence of the velocity parameters of the driving links on the kinematic characteristics of these mechanisms are established.
Keywords: Drive; Biplanetary mechanism; Kinematic parameters; mixing machine.